How does occupational prestige of migrant workers affect farmland transfer in China? - Zerong Wang; Jiaxin Fei; Jie Han (PLoS ONE, 2025)
Occupational prestige, a socioeconomic status metric, has received limited attention in prior studies regarding its influence on farmland transfer. Based on data from the China Family Panel Studies (CFPS) conducted in 2018 and 2020, we analyze the impact of occupational prestige on farmland transfer. The findings reveal that farmers with higher occupational prestige are more likely to transfer their farmland, and the results using the instrumental variable (IV)-Probit model remained significant. Occupational prestige facilitates farmland transfer by enhancing farmers’ awareness of land ownership rights and policies, concurrently diminishing their expectations of land security. Credit-constrained farmers, those with lower income levels, and farmers in the central-western regions of China are more willing to transfer their land. These research insights underscore the significance of fostering inclusive urban employment initiatives and providing upward mobility opportunities for rural migrant workers. Such endeavors are deemed critical for nurturing the development and advancement of China’s rural land rental market.